Experimental study on vortex-induced motions of a semi-submersible platform with four square columns, part III: Effects of the collinear irregular and regular wave incidence and current. (1st December 2020) - Gonçalves, Rodolfo T.; Pinto, Leandro A.; Fujarra, André L.C.
Abstract: Aiming to complete the results presented before in Gonçalves et al. (2012. Ocean Eng. 54, 150–169) and Gonçalves et al. (2013. Ocean Eng. 62, 10–24), this third part of the research work studied the behavior of large-volume SS - semi-submersible platforms due to the VIM - vortex-induced motions under the combined action of current and waves. Small-scale towing tests were carried out to understand the effects of the collinear irregular and regular waves on the VIM of a SS. The results showed that waves influenced the VIM phenomenon and decreased its response amplitudes in specific cases, although the source of this mitigation process does not depend on the wave nature (regular or irregular). Moreover, by using plots of velocity ratio α as function of the K C - Keulegan-Carpenter number, regions of predominance were identified for inertia and viscous forces. The VIM in waves was mitigated for cases with inertia-force predominance, yet it had appeared even in low amplitudes for cases of large K C number at the viscous-force region. Highlights: Simultaneous wave and current test were performed. Irregular and regular wave tests were conducted. Nature of the wave was not the responsible to mitigate the VIM. Motions in the in-line direction were directly responsible for VIM behavior. KC and alpha parameters were the most important parameters.